Did Gregory of Nazianz Write the Epigrams on Antiochus Epiphanes’ Sanctuary of Nemrud Dağ or Not (AP 8, 176–254)? A Commentary on L. Robert’s note in the Bulletin Épigraphique VI, 1968 – 1970, no 619 - Polański, Tomasz (Anabasis. Studia Classica et Orientalia, 2016)
L. Robert suggested that the cycle of epigrams from Book VIII (176–256) of the Palatine Anthology was a lamentation on the destruction of the hierothesion of Nemrud Dağ. The execration epigrams of AP 8, 176–254 are not by Gregory of Nazianz. They belong to the Pagan tradition of the Greek epigrammatic poetry. The collection does not focus on one grave monument, but refers to different burial structures, different settings and in some cases to burial sites, what can be shown through the analysis of the ecphrastic verses in the collection. None of the execration epigrams points to a specified location, which may be suggestive of Kommagene, the Euphrates, and the Taurus Mountains. Some of them are suggestive of a magnificent sanctuary located high up in the mountains (177, 178, 209, 230, 236). There are formal and structural parallels between the execration epigrams AP 8, 176–254 and the royal inscriptions of Kommagene.